The Impact of the Threat of Terrorism on Tourism Growth in East Africa - Diva Pancarani; Seniwati Seniwati (Pusat Riset dan Inovasi Nasional, 2025)
East Africa has great potential in the tourism sector, but is vulnerable to the threat of terrorism that can hinder economic growth and regional stability. This research aims to analyze the impact of terrorism on tourism development, especially in Kenya as a case study. The research uses a Library Research method with a descriptive qualitative approach based on narrative and contextual. The theory used is the tactical definition of terrorism by C.A.J Coady which emphasizes violence against civilians for political interests and Esmailzadeh's perspective which states the adaptive and global nature of terrorism. The results of the analysis show that terror attacks, such as those that occurred in several countries in the East African region, do not only cause physical casualties but also psychological and symbolic impacts in the form of declining tourist numbers, disruption of security perceptions and a negative image of the destination in the eyes of the international community. This study emphasizes the importance of an integrated approach: hard security, inclusive economic development, and soft power-based promotion. The novelty of this research lies in the integration of theoretical-philosophical approaches and empirical data to assess the linkages between security and tourism in conflict-prone areas, which have rarely been studied in depth in the East African context.